A bimetallic bifunctional catalyst for hydrogen production from carbon dioxide hydrogenation and methanol steam reforming and its preparation method

CN122665620APending Publication Date: 2026-09-01CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611014543.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0005]针对现有催化剂在二氧化碳加氢制甲醇和甲醇蒸汽重整制氢反应中存在的活性组分易烧结、稳定性差、双功能催化效率低等技术瓶颈,本发明提供一种用于二氧化碳加氢和甲醇重整双功能催化的催化剂及其制备方法

Benefits of technology

本发明催化剂在CO2加氢制甲醇和甲醇蒸汽重整制氢两个反应中均表现出卓越的催化活性和稳定性。在CO2加氢制甲醇反应中,Pt-Cu双金属的电子协同效应调变了活性中心的d带中心位置,优化了对HCOO中间体的吸附能,同时抑制了逆水煤气变换副反应;在甲醇蒸汽重整制氢反应中,ZnGa2O4尖晶石载体的高热导率有效缓解了强吸热反应中的床层温差问题,经100小时长周期测试,催化剂活性未见明显衰减。本发明通过介孔限域、双金属协同和金属载体强相互作用三级结构设计,构建了高效的催化体系。介孔ZnGa2O4载体通过空间限域作用将Pt-Cu纳米颗粒稳定锚定于孔道内;Pt-Cu双金属体系通过电子转移和晶格应变优化了合金的d带中心位置;ZnGa2O4载体与Pt-Cu金属间形成的强相互作用在界面处诱导出丰富的氧空位,共同构成了催化剂高活性的根本来源。本发明通过Pt-Cu双金属合金结构的构建,实现了对Cu活性中心电子密度的精准调变。Pt的引入导致电子从Cu向Pt转移,使Cu的d带中心下移,一方面削弱了Cu对CO中间体的吸附强度,在CO2加氢反应中有效抑制了CO的生成;另一方面,增强了Cu对含氧中间体的稳定性,促进了甲醇的生成路径。在甲醇重整反应中,Pt-Cu双金属界面提供了双功能活性位点,Cu位点负责甲醇的脱氢活化,Pt位点则促进水煤气变换反应,两者协同作用实现了甲醇的高效转化和氢气的高选择性生成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122665620A_ABST
    Figure CN122665620A_ABST
Patent Text Reader

Abstract

This invention discloses a bimetallic bifunctional catalyst for methanol production via carbon dioxide hydrogenation and hydrogen production via methanol steam reforming, and its preparation method. The catalyst uses an ordered mesoporous Zn-Ga composite oxide spinel as a support, with a Pt-Cu bimetallic component as the active component. The preparation method includes three steps: preparation of the mesoporous composite oxide support, loading of the active component, and reduction activation. By controlling the Zn / Ga molar ratio of the support, calcination parameters, the feed ratio and loading of the bimetallic component, and reduction conditions, the catalyst structure and performance are optimized. Through a three-level structural design of mesoporous confinement, bimetallic synergy, and strong metal-support interaction, this catalyst solves the problems of easy sintering of the active component, poor thermal stability, and low bifunctional catalytic efficiency in traditional copper-based catalysts. It exhibits excellent catalytic activity, selectivity, and long-term stability in both CO2 hydrogenation to methanol and methanol steam reforming to hydrogen production, providing a highly efficient catalytic solution for carbon capture and utilization and hydrogen energy storage and transportation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of catalytic materials and energy chemical technology, specifically relating to a bimetallic bifunctional catalyst for the production of methanol by carbon dioxide hydrogenation and the production of hydrogen by methanol steam reforming, and its preparation method. Background Technology

[0002] With the advancement of global carbon neutrality goals and the rapid development of the hydrogen economy, methanol, as an ideal hydrogen storage medium and basic chemical raw material, has attracted widespread attention for its related catalytic conversion processes. Among these, the hydrogenation of carbon dioxide to methanol enables the resource utilization of greenhouse gases and is a key step in carbon capture and utilization; while methanol steam reforming provides an efficient solution for hydrogen storage and transportation. Therefore, developing efficient and stable catalysts to drive these two reactions has significant academic and industrial value.

[0003] Currently, copper-based catalysts are the most widely studied and maturely applied catalysts for the two reactions mentioned above. However, traditional copper-based catalysts have significant limitations in the following aspects: First, the active component is prone to sintering and has poor thermal stability. In the strongly endothermic methanol steam reforming reaction, copper nanoparticles are prone to migration and aggregation at high temperatures, leading to rapid catalyst deactivation. Second, the electronic structure of a single metal catalyst is difficult to simultaneously optimize the rate-determining steps of two different reactions. Carbon dioxide hydrogenation requires a catalyst to suppress the reverse water-gas shift side reaction, while methanol reforming requires the catalyst to have excellent CH and OH bond breaking capabilities. Third, the interaction between the support and the active metal is weak, limiting the ability to regulate reaction intermediates, and the disordered pore structure of conventional supports provides insufficient confinement of the active component.

[0004] To address the aforementioned issues, researchers have undertaken extensive improvement efforts. Introducing a second metal to form a bimetallic system with copper allows for optimization of the reaction pathway through geometric and electronic effects. Regarding supports, spinel-type composite oxides have become a research hotspot due to their structural stability and tunable surface properties, while the confinement effect of mesoporous materials is beneficial for suppressing metal migration. However, how to organically combine ordered mesoporous spinel supports, bimetallic active components, and the strong interactions between them, and simultaneously apply them to the two important reactions of carbon dioxide hydrogenation and methanol steam reforming, still lacks systematic research. Summary of the Invention

[0005] To address the technical bottlenecks of existing catalysts in the carbon dioxide hydrogenation to methanol and methanol steam reforming to hydrogen reactions, such as easy sintering of active components, poor stability, and low bifunctional catalytic efficiency, this invention provides a bifunctional catalyst for carbon dioxide hydrogenation and methanol reforming catalysis, and its preparation method. This invention aims to improve the catalyst's thermal stability, target product selectivity, and applicability to both reactions by constructing a Zn-Ga composite oxide spinel support with an ordered mesoporous structure and utilizing the synergistic effect of the Pt-Cu bimetallic catalyst.

[0006] To achieve the above objectives, the present invention provides a bimetallic bifunctional catalyst for hydrogen production by carbon dioxide hydrogenation and methanol steam reforming. The catalyst comprises a mesoporous Zn-Ga composite oxide spinel support and a Pt-Cu bimetallic active component supported on the support. A strong metal-support interaction is formed between the support and the Pt-Cu bimetal, and oxygen vacancies are induced at the interface.

[0007] Furthermore, the mesoporous Zn-Ga composite oxide spinel support is a spinel structure with an ordered mesoporous structure, and the molar ratio of Zn to Ga in the Zn-Ga composite oxide is 1:3 to 2:1, preferably 1:1.5 to 1:2.5.

[0008] Furthermore, in the Pt-Cu bimetallic active component, the molar ratio of Pt to Cu is 1:5 to 1:50, and the loading of Pt in the catalyst is 0.1-5 wt%, and the loading of Cu is 2-25 wt%.

[0009] The present invention also provides a method for preparing the above-mentioned catalyst, comprising the following steps: (1) Preparation of mesoporous composite oxide support: Zinc salt and gallium salt are dissolved in an organic solvent in stoichiometric ratio to obtain a mixed precursor solution; a hard template is added to the precursor solution and dried to obtain a solid composite; the solid composite is subjected to a first heat treatment under an inert atmosphere to obtain an oxide composite material; the composite material is subjected to a second heat treatment under an oxygen-containing atmosphere to remove the hard template and obtain a Zn-Ga composite oxide support with a mesoporous structure. (2) Loading of active components: The noble metal precursor solution and the non-noble metal precursor solution are added to the support prepared in step (1), and after aging, filtration, washing and drying, the catalyst precursor is obtained; (3) Reduction and activation: The catalyst precursor obtained in step (2) is subjected to a third heat treatment in a reducing atmosphere to reduce the metal ions and obtain the catalyst.

[0010] Furthermore, in step (1), the temperature of the first heat treatment is 300-500℃, and the temperature of the second heat treatment is 400-800℃.

[0011] Furthermore, in step (2), the noble metal precursor is chloroplatinic acid, the non-noble metal precursor is copper nitrate, and the molar ratio of the noble metal precursor to the non-noble metal precursor is 1:5 to 1:50.

[0012] Furthermore, in step (3), the reducing atmosphere is a mixture of hydrogen and inert gas, with hydrogen accounting for 1%-50% of the volume, and the reduction temperature of the third heat treatment is 200-500℃.

[0013] Furthermore, in step (1), the mesoporous hard template is selected from at least one of CMK-3 and SBA-15; the first heat treatment is performed in an argon or nitrogen atmosphere, and the second heat treatment is performed in an air atmosphere.

[0014] This invention also provides the application of the above-described catalyst or the catalyst prepared by the above method in the reaction of carbon dioxide hydrogenation to methanol, wherein the reaction conditions are: temperature 200-300℃, pressure 1-5 MPa, and gas hourly space velocity 1000-10000 h⁻¹. -1 The molar ratio of H2 / CO2 is 2:1 to 5:1.

[0015] This invention also provides the application of the above-described catalyst or the catalyst prepared by the above method in the reaction of carbon dioxide hydrogenation to methanol, wherein the reaction conditions are: temperature 200-350℃, atmospheric pressure or slightly positive pressure, water-to-methanol molar ratio of 1:1 to 3:1, and gas hourly space velocity of 2000-20000 h⁻¹. -1 .

[0016] The beneficial effects of this invention are: The catalyst of this invention exhibits excellent catalytic activity and stability in both CO2 hydrogenation to methanol and methanol steam reforming to hydrogen. In the CO2 hydrogenation to methanol reaction, the electronic synergistic effect of the Pt-Cu bimetallic matrix modulates the d-band center position of the active center, optimizing the adsorption energy for the HCOO intermediate, while suppressing the reverse water-gas shift side reaction. In the methanol steam reforming to hydrogen reaction, the high thermal conductivity of the ZnGa2O4 spinel support effectively alleviates the bed temperature difference problem in the strongly endothermic reaction, and no significant attenuation of catalyst activity was observed after a 100-hour long-term test. This invention constructs a highly efficient catalytic system through a three-level structural design of mesoporous confinement, bimetallic synergy, and strong metal-support interaction. Mesoporous ZnGa2O4 supports stably anchor Pt-Cu nanoparticles within their pores through spatial confinement. The Pt-Cu bimetallic system optimizes the d-band center position of the alloy through electron transfer and lattice strain. The strong interaction between the ZnGa2O4 support and the Pt-Cu metal induces abundant oxygen vacancies at the interface, collectively constituting the fundamental source of the catalyst's high activity. This invention achieves precise modulation of the electron density of the Cu active center through the construction of a Pt-Cu bimetallic alloy structure. The introduction of Pt leads to electron transfer from Cu to Pt, causing the Cu d-band center to shift downwards. On the one hand, this weakens the adsorption strength of Cu for CO intermediates, effectively inhibiting CO formation in the CO2 hydrogenation reaction; on the other hand, it enhances the stability of Cu for oxygen-containing intermediates, promoting the methanol formation pathway. In the methanol reforming reaction, the Pt-Cu bimetallic interface provides bifunctional active sites: Cu sites are responsible for methanol dehydrogenation activation, while Pt sites promote the water-gas shift reaction. The synergistic effect of both achieves efficient methanol conversion and highly selective hydrogen generation. Attached Figure Description

[0017] Figure 1 The XRD pattern of the mesoporous ZnGa2O4 spinel support prepared in Example 1 of this invention; Figure 2 This is a diagram showing the pore structure of the mesoporous ZnGa2O4 spinel support prepared in Example 1; Figure 3 The graphs show the CO2 hydrogenation performance of the catalysts prepared in Examples 1-5. Figure 4 The graphs show the methanol steam reforming hydrogen production performance of the catalysts prepared in Examples 1-5. Figure 5 The graph shows the CO2 hydrogenation performance of the catalysts prepared in Examples 1, 6-14. Figure 6 The graph shows the methanol steam reforming hydrogen production performance of the catalysts prepared in Examples 1, 6-14. Figure 7The graph shows the CO2 hydrogenation performance of the catalysts prepared in Example 1 and Comparative Examples 1-8. Figure 8 The graph shows the methanol steam reforming hydrogen production performance of the catalysts prepared in Example 1 and Comparative Examples 1-8. Figure 9 This is a long-cycle lifetime graph of the catalyst prepared in Example 1 for CO2 hydrogenation. Figure 10 This is a long-cycle lifetime diagram of the catalyst prepared in Example 1 for methanol steam reforming to produce hydrogen. Detailed Implementation

[0018] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The present invention includes, but is not limited to, the following embodiments.

[0019] Example 1: (1) Preparation of mesoporous composite oxide support: Zinc nitrate and gallium nitrate were accurately weighed according to the stoichiometric ratio of Zn:Ga = 1:2 and fully dissolved in 10 mL of anhydrous ethanol to form a homogeneous mixed precursor solution. Subsequently, 2.0 g of CMK-3 mesoporous carbon was added to the solution as a hard template and placed in an oven at 80°C for 12 hours to allow the metal precursor to fully enter the pores of the carbon template, resulting in a solid composite. The dried solid was carefully ground into a fine powder, evenly spread in a ceramic boat, and transferred to a tube furnace. Under continuous Ar gas protection, the temperature was raised to 400°C at a heating rate of 2°C / min and held at the temperature for 4 hours to allow the nitrate to thermally decompose in the template pores and be converted into oxide, thereby obtaining the CMK-3@Zn-Ga-O oxide composite material. The composite material was placed in a muffle furnace and heated to 600°C in air at a heating rate of 2°C / min and held at that temperature for 6 hours. During this process, the CMK-3 carbon template was completely oxidized and removed, ultimately yielding a mesoporous ZnGa2O4 spinel support. (2) Loading of active components: 2.66 mL of chloroplatinic acid solution with a concentration of 10 mg / mL and 2 mL of copper nitrate solution with a concentration of 0.7 mol / L (Pt:Cu=1:10) were accurately measured and added dropwise to 2 g of the mesoporous ZnGa2O4 support prepared above. The mixture was allowed to stand and age at room temperature and pressure for 12 hours, followed by filtration, washing and drying to obtain the catalyst precursor loaded with active components; (3) Reduction and activation: The obtained catalyst precursor was placed in a tube furnace and heated to 350°C at a heating rate of 3°C / min under a reducing atmosphere of 10% H2 / Ar mixture, and reduced at this temperature for 4 hours. This step reduces the metal ions to the active component, and finally the PtCu / ZnGa2O4 bimetallic catalyst is obtained.

[0020] The performance evaluation of the catalyst for CO2 hydrogenation to methanol was conducted on a fixed-bed microreactor. 0.2 g of catalyst (40 mesh) was mixed with an equal volume of quartz sand and packed into a stainless steel reaction tube. The mixture was heated to 300°C at 5°C / min under an Ar atmosphere, then switched to a 10% H2 / Ar mixed gas for reduction for 4 hours. After reduction, Ar purging was initiated and the temperature was lowered to the reaction temperature (200-300°C). H2 and CO2 were mixed at an H2 / CO2 molar ratio of 2:1 to 5:1 and then introduced into the reactor via a mass flow controller. The reaction pressure was controlled at 3 MPa by a back pressure valve, and the gas hourly space velocity (GHSV) was 10000 h⁻¹. -1 The reaction products were analyzed online by gas chromatography, equipped with TCD and FID detectors, to detect components such as H2, CO, CO2, and methanol, respectively. Stability testing was conducted continuously for 100 hours to monitor the change in catalyst activity over time.

[0021] The performance evaluation of the catalyst for methanol steam reforming to hydrogen production was conducted on a fixed-bed microreactor evaluation device. 0.2 g of catalyst (40 mesh) was mixed with an equal volume of quartz sand and packed into a stainless steel reaction tube. The mixture was heated to 350°C at 5°C / min under an Ar atmosphere, then switched to a 10% H2 / Ar mixed gas for reduction for 4 hours. After reduction, the mixture was purged with N2 and cooled to the reaction temperature (250°C). A mixture of methanol and deionized water at a water-to-methanol molar ratio of 2:1 was prepared and pumped by a high-pressure constant-flow pump to a 150°C preheating vaporizer for complete vaporization before being introduced into the reactor. The reaction pressure was atmospheric pressure, and the gas hourly space velocity (GHSV) was 10000 h⁻¹. -1 The reaction products were analyzed online by gas chromatography, equipped with TCD and FID detectors, to detect each component separately. Stability testing was conducted continuously for 100 hours to monitor changes in catalyst activity and product composition.

[0022] Example 2 The difference between this embodiment and embodiment 1 is that in step (1), Zn:Ga = 1:2 is changed to Zn:Ga = 2:1, while other conditions remain unchanged.

[0023] Example 3 The difference between this embodiment and embodiment 1 is that in step (1), Zn:Ga = 1:3, while other conditions remain unchanged.

[0024] Example 4 The difference between this embodiment and embodiment 1 is that the calcination temperature of the composite material in the muffle furnace in step (1) is changed from 600℃ to 400℃, while other conditions remain unchanged.

[0025] Example 5 The difference between this embodiment and embodiment 1 is that the calcination temperature of the composite material in the muffle furnace in step (1) is changed from 600℃ to 800℃, while other conditions remain unchanged.

[0026] Example 6 The difference between this embodiment and embodiment 1 is that in step (2), Pt:Cu=1:10 is changed to Pt:Cu=1:5, while other conditions remain unchanged.

[0027] Example 7 The difference between this embodiment and embodiment 1 is that in step (2), Pt:Cu=1:10 is changed to Pt:Cu=1:20, while other conditions remain unchanged.

[0028] Example 8 The difference between this embodiment and embodiment 1 is that in step (2), Pt:Cu=1:10 is changed to Pt:Cu=1:30, while other conditions remain unchanged.

[0029] Example 9 The difference between this embodiment and Example 1 is that in step (2), 2.66 mL of chloroplatinic acid solution with a concentration of 10 mg / mL is changed to 1.33 mL, while other conditions remain unchanged.

[0030] Example 10 The difference between this embodiment and Example 1 is that in step (2), the 2.66 mL of chloroplatinic acid solution with a concentration of 10 mg / mL is changed to 3.32 mL, while other conditions remain unchanged.

[0031] Example 11 The difference between this embodiment and Example 1 is that in step (2), 2 mL of 0.7 mol / L copper nitrate solution is replaced with 1 mL, while other conditions remain unchanged.

[0032] Example 12 The difference between this embodiment and Example 1 is that in step (2), 2 mL of 0.7 mol / L copper nitrate solution is replaced with 3 mL, while other conditions remain unchanged.

[0033] Example 13 The difference between this embodiment and embodiment 1 is that the reduction temperature in step (3) is changed from 350℃ to 250℃, while other conditions remain unchanged.

[0034] Example 14 The difference between this embodiment and embodiment 1 is that the reduction temperature in step (3) is changed from 350℃ to 450℃, while other conditions remain unchanged.

[0035] Comparative Example 1 The difference between this comparative example and Example 1 is that no hard template is added in step (1), while other conditions remain unchanged; Comparative Example 2 The difference between this comparative example and Example 1 is that in step (2), palladium acetate solution is used instead of chloroplatinic acid solution, while other conditions remain unchanged; Comparative Example 3 The difference between this comparative example and Example 1 is that in step (2), ruthenium chloride solution is used instead of chloroplatinic acid solution, while other conditions remain unchanged; Comparative Example 4 The difference between this comparative example and Example 1 is that in step (2), rhodium acetate solution is used instead of chloroplatinic acid solution, while other conditions remain unchanged; Comparative Example 5 The difference between this comparative example and Example 1 is that in step (2), iridium chloride solution is used instead of chloroplatinic acid solution, while other conditions remain unchanged; Comparative Example 6 The difference between this comparative example and Example 1 is that in step (2), nickel nitrate solution is used instead of copper nitrate solution, while other conditions remain unchanged; Comparative Example 7 The difference between this comparative example and Example 1 is that in step (2), ferric nitrate solution is used instead of copper nitrate solution, while other conditions remain unchanged; Comparative Example 8 The difference between this comparative example and Example 1 is that in step (2), the cobalt nitrate solution is used instead of the copper nitrate solution, while other conditions remain unchanged.

[0036] Figure 1 The XRD pattern of the mesoporous ZnGa2O4 spinel support prepared in Example 1 is shown. Distinct characteristic diffraction peaks appear at 2θ = 30.2°, 35.6°, 43.1°, 57.2°, and 62.8°, corresponding to the (220), (311), (400), (511), and (440) crystal planes of the spinel structure, respectively, which highly coincide with the diffraction peak positions of standard spinel ZnGa2O4. No impurity peaks of ZnO or Ga2O3 were detected in the pattern, indicating that a pure-phase spinel support was successfully prepared using the hard template method. The formation of the pure-phase spinel structure is the basis for constructing strong metal-support interactions, providing structural assurance for the subsequent stable anchoring of the Pt-Cu bimetal and the formation of interfacial oxygen vacancies.

[0037] Figure 2The figure shows the nitrogen adsorption-desorption isotherm of the mesoporous ZnGa2O4 spinel support prepared in Example 1. The figure reveals a highly ordered mesoporous channel structure with regular channel arrangement. This ordered mesoporous structure has three main functions: firstly, spatial confinement can stably anchor Pt-Cu nanoparticles within the channels, effectively suppressing migration and sintering during high-temperature reactions; secondly, the mesoporous channels act as nanoreactors, enhancing the enrichment and collision probability of reactant molecules and increasing the reaction rate; and thirdly, the regular mesoporous structure provides rapid diffusion channels for reactants and products, shortening the residence time of carbon deposition precursors and endowing the catalyst with excellent anti-carbon deposition capabilities.

[0038] Figure 3 This is a comparison of the performance of the catalysts prepared in Examples 1-5 for the CO2 hydrogenation to methanol reaction. As can be seen from the figures, in Example 1, with a Zn:Ga ratio of 1:2 and a support calcination temperature of 600°C, the catalyst exhibited the highest CO2 conversion and methanol selectivity. When the Zn:Ga ratio deviated from 1:2 in Examples 2 and 3, impurity phases appeared in the spinel structure, weakening the metal-support interaction and leading to a decrease in catalytic performance. In Example 4, when the support calcination temperature was too low, the spinel crystallization was incomplete, resulting in insufficient surface oxygen vacancies and limited CO2 activation capacity. In Example 5, when the calcination temperature was too high, the mesoporous structure collapsed, the specific surface area decreased significantly, and the dispersion of the active component decreased.

[0039] Figure 5 The graphs show a comparison of the performance of the catalysts prepared in Examples 1 and 6-14 for the CO2 hydrogenation to methanol reaction, investigating the effects of factors such as the Pt:Cu ratio, metal loading, and reduction temperature. The graphs show that in Example 1, the Pt:Cu ratio of 1:10 and the reduction temperature of 350°C exhibited the best performance. When the Pt:Cu ratio in Examples 6-8 deviated from the optimal range, the bimetallic synergistic effect weakened. In Example 6, when the Pt ratio was too high, Pt atoms aggregated to form large particles, reducing the number of active sites. In Examples 7-8, when the Pt ratio was too low, the modulation effect of Pt on the electronic structure of Cu was insufficient, and the downward shift of the d-band center was inadequate. The effect of reduction temperature in Examples 13-14 indicates that 350°C is the optimal reduction temperature. At lower temperatures, metal reduction is insufficient, resulting in an inadequate number of active centers; at higher temperatures, metal particles sinter. Figure 6The graph shows a comparison of the performance of the catalysts prepared in Examples 1 and 6-14 for methanol steam reforming to produce hydrogen. As can be seen from the graph, the performance trends of each example are highly consistent with those of the CO2 hydrogenation reaction, with Example 1 still showing the best performance. It is noteworthy that the Pt:Cu ratio has a more significant impact on the methanol reforming reaction. When the Pt ratio is too low, the activation capacity of the Cu sites for methanol dehydrogenation is insufficient, and the lack of Pt sites to promote the water-gas shift reaction leads to an increase in CO content in the product gas and a decrease in hydrogen yield. When the Pt ratio is too high, the utilization rate of precious metals decreases, and excessive Pt may promote the methanol decomposition pathway, reducing hydrogen selectivity. This result fully confirms the dual-functional active site mechanism of Cu sites being responsible for methanol dehydrogenation and Pt sites promoting water-gas shift reaction.

[0040] Figure 7 The graph shows a comparison of the CO2 hydrogenation to methanol reaction performance between Example 1 and Comparative Examples 1-8. As can be seen from the graph, the CO2 conversion rate and methanol selectivity of Example 1 are significantly better than all the comparative examples. Comparative Example 1, lacking a mesoporous structure, exhibits a significant decrease in catalytic performance, highlighting the importance of the mesoporous confinement effect. Comparative Examples 2-5, using different noble metals to replace Pt, and Comparative Examples 6-8, using different non-noble metals to replace Cu, all show lower catalytic performance than Example 1, confirming the optimality of the Pt-Cu combination in the bimetallic synergistic effect. This comparison fully verifies the unique advantages of the mesoporous spinel support and Pt-Cu bimetallic system of this invention in the CO2 hydrogenation reaction. The underlying mechanism lies in the precise modulation of the d-band center by the Pt-Cu electronic synergistic effect, optimizing the adsorption energy of key intermediates, and effectively suppressing the reverse water-gas shift side reaction.

[0041] Figure 8 The graph shows a comparison of the methanol steam reforming hydrogen production performance of Example 1 and Comparative Examples 1-8. As can be seen from the graph, the methanol conversion rate and hydrogen yield of Example 1 are significantly better than all the comparative examples. In Comparative Example 1, the lack of a mesoporous structure leads to a lack of confinement effect, resulting in easy sintering of the metal particles and poor stability. Comparative Examples 2-5 and 6-8, due to insufficient bimetallic synergistic effect, exhibit lower methanol dehydrogenation activity and water-gas shift activity compared to the Pt-Cu combination. This result further confirms that the synergistic effect of the mesoporous confinement effect and the Pt-Cu bimetallic synergistic effect is key to achieving bifunctional catalytic performance.

[0042] Figure 9The figures show the long-term stability test results of the catalyst prepared in Example 1 in the CO2 hydrogenation to methanol reaction. As can be seen from the figures, after 100 hours of continuous operation, the methanol yield decreased by less than 5%, indicating that the catalyst has excellent stability. This stability stems from a triple mechanism: firstly, the spatial confinement effect of the mesoporous ZnGa2O4 support stably anchors the Pt-Cu nanoparticles within the pores, effectively inhibiting migration and sintering; secondly, the strong metal-support interaction between ZnGa2O4 and Pt-Cu induces abundant oxygen vacancies at the interface, which not only participate in CO2 activation but also enhance the anchoring strength of the metal particles; and thirdly, the well-organized mesoporous structure provides rapid diffusion channels, shortening the residence time of the carbon deposition precursor.

[0043] Figure 10 The figure shows the long-term stability test results (100 hours) of the catalyst prepared in Example 1 in the methanol steam reforming hydrogen production reaction. As can be seen from the figure, after 100 hours of continuous operation, the methanol conversion rate remained stable at over 98%, far superior to the traditional Cu / ZnO / Al2O3 catalyst. This excellent stability also stems from the synergistic protection of the mesoporous confinement effect and the strong metal-support interaction. It is worth noting that in the strongly endothermic methanol reforming reaction, the high thermal conductivity of the ZnGa2O4 spinel support effectively alleviated the bed temperature difference problem and avoided metal sintering caused by hot spot formation. This is also an important reason why the catalyst maintained excellent stability in the 100-hour long-term test.

[0044] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A bimetallic bifunctional catalyst for hydrogen production via carbon dioxide hydrogenation and methanol steam reforming, characterized in that, The catalyst comprises a mesoporous Zn-Ga composite oxide spinel support and a Pt-Cu bimetallic active component supported on the support; a strong metal-support interaction is formed between the support and the Pt-Cu bimetal, and oxygen vacancies are induced at the interface.

2. The catalyst according to claim 1, characterized in that, The mesoporous Zn-Ga composite oxide spinel carrier is a spinel structure with an ordered mesoporous structure, and the molar ratio of Zn to Ga in the Zn-Ga composite oxide is 1:3 to 2:1, preferably 1:1.5 to 1:2.

5.

3. The catalyst according to claim 1, characterized in that, In the Pt-Cu bimetallic active component, the molar ratio of Pt to Cu is 1:5 to 1:50, and the loading of Pt in the catalyst is 0.1-5 wt% and the loading of Cu is 2-25 wt%.

4. A method for preparing the catalyst according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Preparation of mesoporous composite oxide support: Zinc salt and gallium salt are dissolved in an organic solvent in stoichiometric ratio to obtain a mixed precursor solution; a hard template is added to the precursor solution and dried to obtain a solid composite; the solid composite is subjected to a first heat treatment under an inert atmosphere to obtain an oxide composite material; the composite material is subjected to a second heat treatment under an oxygen-containing atmosphere to remove the hard template and obtain a Zn-Ga composite oxide support with a mesoporous structure. (2) Loading of active components: The noble metal precursor solution and the non-noble metal precursor solution are added to the support prepared in step (1), and after aging, filtration, washing and drying, the catalyst precursor is obtained; (3) Reduction and activation: The catalyst precursor obtained in step (2) is subjected to a third heat treatment in a reducing atmosphere to reduce the metal ions and obtain the catalyst.

5. The preparation method according to claim 4, characterized in that, In step (1), the temperature of the first heat treatment is 300-500℃, and the temperature of the second heat treatment is 400-800℃.

6. The preparation method according to claim 4, characterized in that, In step (2), the noble metal precursor is chloroplatinic acid, the non-noble metal precursor is copper nitrate, and the molar ratio of the noble metal precursor to the non-noble metal precursor is 1:5 to 1:

50.

7. The preparation method according to claim 4, characterized in that, In step (3), the reducing atmosphere is a mixture of hydrogen and inert gas, with hydrogen accounting for 1%-50% of the volume, and the reduction temperature of the third heat treatment is 200-500℃.

8. The preparation method according to claim 4, characterized in that, In step (1), the mesoporous hard template is selected from at least one of CMK-3 and SBA-15; the first heat treatment is carried out in an argon or nitrogen atmosphere, and the second heat treatment is carried out in an air atmosphere.

9. The use of the catalyst according to any one of claims 1-3 or the catalyst prepared by the method according to any one of claims 4-8 in the reaction of carbon dioxide hydrogenation to methanol, characterized in that, The reaction conditions are: temperature 200-300℃, pressure 1-5 MPa, and gas hourly space velocity 1000-10000 h⁻¹. -1 The molar ratio of H2 / CO2 is 2:1 to 5:

1.

10. The use of the catalyst according to any one of claims 1-3 or the catalyst prepared by the method according to any one of claims 4-8 in the methanol steam reforming hydrogen production reaction, characterized in that, The reaction conditions are as follows: temperature 200-350℃, atmospheric or slightly positive pressure, water-to-ethanol molar ratio of 1:1 to 3:1, and gas hourly space velocity of 2000-20000 h⁻¹. -1 .